Supplemental progesterone increases pregnancy rates and embryo survival in lactating dairy cows - S. Z. El-Zarkouny; J. A. Cartmill; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1999)
Administering progesterone to lactating dairy cows has sometimes proven effective in increasing pregnancy rates. In this study, cows were treated with the Ovsynch protocol in addition to supplemental progesterone given for 7 days between the first gonadotropin- releasing hormone (GnRH) injection and the prostaglandin F2á (PGF2á) injection. Conception rates were greater in lactating Holstein dairy cows receiving exogenous progesterone (62.5%) than in controls treated with only the Ovsynch protocol (35.5%). In addition, progesterone supplementation increased embryo survival between 28 and 56 days of pregnancy.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Ovsynch protocol; Progesterone; Lactating cows; Pregnancy rates